Active Methodologies in the Classrooms (International Journal of Psychosocial Rehabilitation, 2020)
Active methodologies applied by teachers in classrooms are interactive processes where the protagonist and builder of their own knowledge is the student with the guidance of a mediator, facilitator, or teacher. These educational processes respond to the new demands and needs of the apprentice and of society. The objective was to determine the type of methodology used by teachers in classrooms and in areas of action before the ignorance in the educational process applied by the teachers in the classrooms. The bibliographic method, the inductive-deductive correlational method, was used, applying the survey as an instrument with a questionnaire with structured questions to gain knowledge of the reality of the educational processes used by teachers. The information gathered led to the deduction that teachers have basic knowledge in active methodologies and apply them based on learning problems from 2nd to 7th year of General Basic Education and upper primary, corresponding to 8th, 9th, and 10th, they use collaborative learning.